Pergeseran Nilai-Nilai Kesakralan Pada Pernikahan: - Sefiyani, Dewi; Wardan, Enda; Nurhidayati, Riezka; Debana, Muhammad Zaky; Saiin, Asrizal (Mabahits : Jurnal Hukum Keluarga Islam, 2024)
The majority of Indonesians still consider marriage to be a sacred agreement, as shown by the various events and traditions that accompany it, many people wish to marry once in their lifetime. However, the increasing number of divorces calls into question the sanctity of marriage. In early May 2024 the judge granted Ria Ricis' divorce lawsuit against Teuku Ryan. This research aims to understand marriage in the Civil Code and KHI law, as well as the sacred values ​​of marriage and divorce according to Islamic law and the causes of their occurrence. The author will examine the impulses that cause a shift in sacred values ​​in marriage which causes divorce. This type of qualitative research uses data collection methods using literature, both secondary and primary data. From the findings, marriage is the union of two people who have the same belief or religion. The sacred values ​​in marriage are found when the marriage contract takes place. Divorce is the severance of the relationship between husband and wife and the loss of sacred values ​​in marriage. There are several factors that cause divorce: economic, betrayal, and finally social and cultural. The shift in sacred values ​​in Ria Ricis's marriage was caused by several incentives, First: interference from her in-laws, Second: poor communication, Third: mental support was not met, Fourth: physically insulting the wife. The disputes and disputes that caused the ongoing conflict in Ria Ricis and Teuku Ryan's household were difficult to resolve, so their relationship became unstable and difficult to repair, causing a significant rift. As a result, Ria Ricis and Teuku Ryan's household was destroyed.